Regio- and Diastereoselective Vicinal Aminobromination of Electron Deficient Olefins via Phosphorus-Based GAP Protocol - Rahman, Anis Ur; Zarshad, Nighat; Khan, Iltaf; Faiz, Faisal; Li, Guigen; Ali, Asad (Frontiers in Chemistry, 2021)
Chemical synthesis based on Group-Assisted Purification chemistry (GAP) has been prolifically used as a powerful, greener and ecofriendly tool so far. Herein, we report hypervalent iodine (III) mediated regio- and diastereoselective aminobromination of electron-deficient olefins using group-assisted purification (GAP) method. By simply mixing the GAP auxiliary-anchored substrates with TsNH2–NBS as nitrogen/bromine sources and PhI(OAc)2 as a catalyst, a series of vicinal bromoamines with multifunctionalities were obtained in moderate to excellent yields (53–94%). The vicinal bromoamines were obtained without column chromatography and/or recrystallization simply by washing the crude mixtures with cosolvents and thus avoiding wastage of silica, solvents, time, and labor. The GAP auxiliary is recyclable and reusable.